MORBIDITY AND MORTALITY FROM COVID-19 IN A DIALYSIS CENTER IN NORTHERN BULGARIA - Biser Borisov; Elena Borisova; Desislava Lubomirova; Pavlina Glogovska (Peytchinski Publishing, 2022)
Purpose: Since its inception in early 2020, COVID-19 has quickly become a pandemic, killing more than six million people worldwide. The aim of this study is to investigate the morbidity and mortality of COVID-19 in one Bulgarian hemodialysis center. Materials and methods: The study is retrospective, conducted for the period of 25th Apr 2020 - 31st Dec 2021. The mean annual number of hemodialysis patients was 184, including patients with end-stage renal disease and acute renal failure. The total number of patients with COVID-19 was 78 (42%), 49of which (63%) were males, the average age was 60 years (+/-12.1 years). Results: There was no significant difference between the mean age of patients divided by sex (p=0.069). A total of 33 people died (42%), 17 of whom (51%) were males. The average age of the deceased patients (64.24 +/- 10.846) was higher than that of the survivors (58.44 +/-12.286), and the difference was significant (p=0.034). There was no significant difference in the mean age of survived and deceased males (p=0.74) but for females, the difference was statistically significant - the mean age of survivorswas 55.00 (+/-12.03)and of the deceased patients was 67.6 (+/- 8.79) years. Conclusion: Our results confirm data from similar studies aboutthe high incidence and mortality of COVID-19 in hemodialysis patients. We confirma statistically significant increase in mortality of these patients with increasing age. Probably the mass vaccination of patients and staff; the use of antiviral drugs and biological therapy is the way to reduce morbidity and mortality among them.